Penyelesaian atas Sertipikat Tanah Ganda Menurut Peraturan Pemerintah Nomor 24 Tahun 1997 Tentang Pendaftaran Tanah (Studi Putusan: Putusan Mahkamah Agung Nomor 1537 K/PDT/2018) - Vanesia Hendrika Elvina; Hasni Hasni (Jurnal Hukum Adigama, 2019)
The purpose of implementing land registration is to provide legal certainty and legal protection. The Agrarian Law that is used in Indonesia adheres to a negative system that is tied to a positive system. The land registration activity for the first time produced proof of rights, in the form of certificates as a means of proof of land rights. Certificate as a strong proof of rights means that physical data and juridical data in a certificate have the strength of evidence and must be accepted as true information, as long as it is not proven otherwise with other evidence in the form of certificates or other certificates. In Subari’s case, there was a double land certificate in the same plot of land. Subari has the ownership of land rights that is got from his parents and from purchasing with two buffaloes. But, there are other people who dominate the land that is belong to Subari and they also have the certificate to proof their ownership of the land rights. Settlement of multiple land certificates can be done through the Court, to obtain legal certainty that the certificate of ownership of land rights which has stronger evidence is based on evidence. The district court ruled that ownership of land rights belonged to Subari, and this decision was reinforced by high court and a Supreme Court.[F1]  [F1]Paragarf single